2021
DOI: 10.1371/journal.pone.0261201
|View full text |Cite
|
Sign up to set email alerts
|

Implications of OPRM1 and CYP2B6 variants on treatment outcomes in methadone-maintained patients in Ontario: Exploring sex differences

Abstract: Genetic variants in the OPRM1 and CYP2B6 genes, respectively coding for an opioid receptor and methadone metabolizers, have been linked to negative treatment outcomes in patients undergoing methadone maintenance treatment, with little consensus on their effect. This study aims to test the associations between pre-selected SNPs of OPRM1 and CYP2B6 and outcomes of continued opioid use, relapse, and methadone dose. It also aims to observe differences in associations within the sexes. 1,172 participants treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The OPRM1 rs1799971 variant was previously examined in the context of methadone maintenance treatment in the START and GENOA trials, both of which used biochemically verified urine screens, however, neither trial looked at genetic effects on abstinence. 37,40 In the end points examined by these trials, there was no evidence of an association of rs1799971 with relapse, continued opioid use, or dose in the GENOA trial, or with dropout or dose in the trial. In the OPTIMA trial, we were able to analyze dropout as an exploratory measure, where we also found no difference by rs1799971 genotype, consistent with the START trial (Table S7); dropout may be influenced more by non-genetic factors, such as dose, number of comorbidities, and administration of other medications.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The OPRM1 rs1799971 variant was previously examined in the context of methadone maintenance treatment in the START and GENOA trials, both of which used biochemically verified urine screens, however, neither trial looked at genetic effects on abstinence. 37,40 In the end points examined by these trials, there was no evidence of an association of rs1799971 with relapse, continued opioid use, or dose in the GENOA trial, or with dropout or dose in the trial. In the OPTIMA trial, we were able to analyze dropout as an exploratory measure, where we also found no difference by rs1799971 genotype, consistent with the START trial (Table S7); dropout may be influenced more by non-genetic factors, such as dose, number of comorbidities, and administration of other medications.…”
Section: Discussionmentioning
confidence: 96%
“…Variation in metabolic enzymes can result in a difference in plasma concentrations of a treatment drug; if important to outcomes, this could manifest as a different effective dose and/or a different response. 36,40 For example, an individual with lower plasma methadone, due to variants associated with faster methadone metabolism, may have worse treatment outcomes, and physicians may increase methadone dosage to adjust for this. As dose is tailored to each individual response, 32 this may partly explain why variants related to metabolism had no effect on non-treatment OFUS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations